Volatile Emissions of Ammonium Nitrate under Flowing Conditions. Issue 5 (9th June 2015) - Steinkamp, Frank Lucus; Giordano, Braden; Collins, Greg; Rose‐Pehrsson, Susan
Abstract Ammonium nitrate (AN) is an ionic solid commonly used as a fertilizer and in commercial blasting applications. Frequently, AN is mixed with a fuel and used in improvised explosives devices (IEDs). To characterize the low‐volatility components emanating from AN, a sample of AN was sealed inside a stainless steel chamber while a laminar flow of air swept the headspace vapor components into a water impinger or cold‐trap for pre‐concentration and subsequent analysis by ion chromatography (IC). Both collection methods were found to be 100 % efficient for collecting nitric acid vapor, whereas the collection efficiency for ammonia was dependent upon the collection method and, for the water impinging method, additionally upon the vapor concentration, humidity and flow rate. Cold‐trapping efficiency for ammonia was 4 %±2 % across all parameters studied. Water impinging was more efficient (20–70 %), but the efficiency varied according to each of the aforementioned variables. The characteristics of an AN vapor generated from a solid sample were found to vary as the sample approached equilibrium inside the chamber. Initially, large quantities of ammonia were observed, but as a steady state was achieved within the laminar flow and a dynamic equilibrium established, the ratio of ammonia to nitric acid in the effluent vapor dropped, although never becoming equimolar. The ratio was strongly dependent upon humidity.